Self-reported hearing performance in workers exposed to solvents - Fuente, Adrian; McPhersonY, Bradley; Hormazabal, Ximena (Revista de Saúde Pública, 2013)
OBJECTIVE: To compare hearing performance relating to the peripheral and central auditory system between solvent-exposed and non-exposed workers. METHODS: Forty-eight workers exposed to a mixture of solvents and 48 non-exposed control subjects of matched age, gender and educational level were selected to participate in the study. The evaluation procedures included: pure-tone audiometry (500 - 8,000 Hz), to investigate the peripheral auditory system; the Random Gap Detection test, to assess the central auditory system; and the Amsterdam Inventory for Auditory Disability and Handicap, to investigate subjects' self-reported hearing performance in daily-life activities. A Student t test and analyses of covariance (ANCOVA) were computed to determine possible significant differences between solvent-exposed and non-exposed subjects for the hearing level, Random Gap Detection test and Amsterdam Inventory for Auditory Disability and Handicap. Pearson correlations among the three measures were also calculated. RESULTS: Solvent-exposed subjects exhibited significantly poorer hearing thresholds for the right ear than non-exposed subjects. Also, solvent-exposed subjects exhibited poorer results for the Random Gap Detection test and self-reported poorer listening performance than non-exposed subjects. Results of the Amsterdam Inventory for Auditory Disability and Handicap were significantly correlated with the binaural average of subject pure-tone thresholds and Random Gap Detection test performance. CONCLUSIONS: Solvent exposure is associated with poorer hearing performance in daily life activities that relate to the function of the peripheral and central auditory system.